2006
DOI: 10.1007/s11162-006-9019-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of community college attendance on baccalaureate attainment

Abstract: Community colleges are seen as contradictory institutions. Supporters contend that community colleges increase baccalaureate attainment by providing access to higher education for students who would otherwise not attend college, while critics argue that these institutions decrease baccalaureate attainment for students who would otherwise attend a 4-year institution. Using the National Education Longitudinal Study, this article advances the literature on the impact of community colleges on baccalaureate attainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 39 publications
3
113
0
Order By: Relevance
“…Pascarella and Terenzini's (2005) found that starting one's college education at a community college reduced the likelihood of completing a bachelor's degree by 15 -20%. This finding is supported in other studies (Alfonso, 2006;Long & Kurlaender, 2009;Reynolds, 2012). Melguizo and Dowd (2009) disagreed; they found that, by controlling for differences in socioeconomic status and for state-level transfer policies, the negative effect that starting at a community college has on degree completion disappeared (p. 77).…”
Section: Transfer Successsupporting
confidence: 89%
See 1 more Smart Citation
“…Pascarella and Terenzini's (2005) found that starting one's college education at a community college reduced the likelihood of completing a bachelor's degree by 15 -20%. This finding is supported in other studies (Alfonso, 2006;Long & Kurlaender, 2009;Reynolds, 2012). Melguizo and Dowd (2009) disagreed; they found that, by controlling for differences in socioeconomic status and for state-level transfer policies, the negative effect that starting at a community college has on degree completion disappeared (p. 77).…”
Section: Transfer Successsupporting
confidence: 89%
“…Scholars have examined the influences of demographic factors, such as socioeconomic status (Wang, 2009;Melguizo & Dowd, 2009), gender (Freeman, Conley & Brooks, 2006;Mourad & Hong, 2011), and race and ethnicity (Mourad & Hong;Wang, 2012;Crisp & Nunez, 2014) on whether transfer students stay in school and attain degrees. Research has also examined transfer student persistence through the lenses of attitude and motivation, previous attendance at a community college, academic performance prior to transfer, and extracurricular involvement (Pascarella & Terenzini, 2005;Alfonso, 2006;Townsend, 2007;Long & Kurlaender, 2009;Wang, 2009;Monaghan & Attewell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…first-time freshmen mainly graduated in the late terms (8 th to 12 th ) while new transfers mainly graduated in the early terms (4 th to 8 th ). Evidence suggests that students who transferred to other institutions have lower degree completion rates than students who began and complet-ed their tenure at the same institutions (Alfonso, 2006;Davis, 2012;Dennis, Calvillo, and Gonzalez, 2008;Handel & Williams, 2013;Laanan, 2001;Li, 2010;Monaghan & Attewell, 2015;Peter, Cataldi, & Carroll, 2005). Credit loss, remediation enrollment, and lack of major prerequisites have been identified as mechanisms that influence transfer students' pathways to degree completion (Attewell, Heil, & Reisel, 2012;Bailey, Jaggars, & Jenkins, 2015;Scott-Clayton, Crosta, & Belffield, 2014).…”
Section: Datamentioning
confidence: 99%
“…Third, Latinos who attend community colleges rarely transfer to 4-year colleges (Yosso & Solorzano, 2006). Alfonso (2006) and others have even argued that attending a two year versus a four year college actually decreases one's chance of graduating with a Bachelor's degree. Finally, among Latinos there are a disproportionate number of part time college students (Solorzano & Ornelas, 2002;Yosso & Solorzano, 2006).…”
Section: Significance Of the Studymentioning
confidence: 99%